Astaxanthin as a potential therapeutic agent for knee osteoarthritis: A review of mechanisms and clinical evidence - Sidra Sabir; AHM Mahmudur Rahman; Abdul Haseeb Bhutta (Bangabandhu Sheikh Mujib Medical University Journal)
Bakground: Knee osteoarthritis (KOA) poses an important challenge in musculoskeletal healthcare, prompting the need for innovative therapeutic strategies. Astaxanthin, a potent antioxidant carotenoid, has gained interest due to its multifaceted mechanisms of action and potential role in KOA management. This review aims to examine the therapeutic mechanisms of astaxanthin in KOA, alongside clinical evidence supporting its effectiveness through a narrative synthesis of preclinical and clinical studies.